Plataformas digitais: o impacto da governança na captura de valor pelos complementadores - Silva, Nubia Adriane da (Universidade do Vale do Rio dos Sinos, 2024)
Digital platforms have emerged as predominant organizational structures in various sectors, promoting innovative ecosystems that integrate actors, architecture and governance. Although the literature on platform governance has grown significantly, most approaches focus on the perspective of the platforms themselves. To enrich this field of study from a new perspective, this research seeks to understand the relationship between the governance mechanisms used by digital platforms and the capture of value by their complementors. To achieve this objective, the research was conducted using a qualitative approach, employing field research. Initially, a Systematic Literature Review (SLR) was carried out on platform governance. From this review, a conceptual framework emerged with three dimensions for the governance structure: (i) coordination (value and control); (ii) design (architecture, access, leadership structure and decision-making); and (iii) value creation mechanisms (resource management, understanding of functions and exclusivity relationships). This framework served as the basis for collecting data on the platforms and their complementors. The research focused on the food service sector. To analyze the platforms, documents related to governance were taken into account, available on the websites and apps of these companies, as well as secondary data from reports and other publications. To understand the complementors' perspective, representatives of 54 companies that transact their food products and services on digital platforms were interviewed. The results showed that governance standards applied uniformly to all actors have a significant impact on the development of complementors' activities, directly influencing their capacity for interaction and innovation and, consequently, value capture. The contributions of this thesis include the proposition of a conceptual governance framework that can deepen understanding of any type of platform and facilitate comparisons between different platforms, as well as providing the complementors' perspective on how governance impacts value capture.
Keywords: Plataformas digitais; Governança; Complementadores; Digital platforms; Governance; Complementors; ACCNPQ::Engenharias::Engenharia de Produção